2007
DOI: 10.1097/01.paf.0000257399.58935.28
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil Toxicity

Abstract: Verapamil blocks the rapid influx of calcium into the cardiac myocytes of the cardiac conduction system and smooth muscle of the vasculature, resulting in decreased myocardial contractility, prolonged conduction time, and vascular relaxation. A sustained-release form, verapamil SR (or ER), is available that contains higher levels of medication and requires only once-daily dosing. The majority of reported fatal cases of verapamil toxicity are due to massive, intentional overdoses. Herein, we present an unusual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…1B, upper panel). In the context of well documented toxicity of VER (17,18), the maximal range of systemic verapamil concentrations that have been achieved in the clinic by rapid continuous intravenous An exponential-phase culture of M. abscessus CIP104536 T (smooth variant) was serially 10-fold diluted, and 5-l volumes of each dilution were spotted onto the agar plates, which were then incubated at 37°C for 4 days before pictures were taken. (B) Line graph showing a hyperbolic decrease in BDQ MIC as the VER concentration is increased (top panel).…”
mentioning
confidence: 99%
“…1B, upper panel). In the context of well documented toxicity of VER (17,18), the maximal range of systemic verapamil concentrations that have been achieved in the clinic by rapid continuous intravenous An exponential-phase culture of M. abscessus CIP104536 T (smooth variant) was serially 10-fold diluted, and 5-l volumes of each dilution were spotted onto the agar plates, which were then incubated at 37°C for 4 days before pictures were taken. (B) Line graph showing a hyperbolic decrease in BDQ MIC as the VER concentration is increased (top panel).…”
mentioning
confidence: 99%
“…Earlier reports have suggested that slow release verapamil can cause acute toxic effects (slow cardiac rhythms and hypotension) in patients with chronic renal failure [2,3]. Death with 720 mg sustained release verapamil has also been reported [4]. Though our patient was on therapeutic doses, she was taking a dose in the higher range of the recommended.…”
Section: Discussionmentioning
confidence: 63%
“…Tarka® is an antihypertensive drug that is approved by US Food and Drug Administration and contains combination of verapamil SR and trandolapril (4) . Verapamil is a calcium channel blocker (CCB).…”
Section: Discussionmentioning
confidence: 99%
“…A significant part, and metabolites of verapamil (70%) are excreted through kidneys. Due to the wide usage area of verapamil and verapamil SR, numerous intoxication cases are reported in the literature (4) . Trandolapril is an angiotensin-converting enzyme inhibitor (ACE-I) and it reduces the angiotensin II level which is a potent vasoconstructor and decreases systemic blood pressure (6) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation